Isolation and identification of the cis-abienol degrading strain Klebsiella oxytoca T2L and its aroma products - Li Han; Xinlong Zhang; Hang Xu; Gaolei Xi; Ke Wang; Haoyang Chen; Wenyuan Qi; Liuke Zhang; Shen Huang (Scientific Reports)
Abstract Cis-abienol, a naturally occurring labdanum diterpenoid, is believed to be an essential precursor of ambergris substances and is found on the surface of many plants. In this study, the strain Klebsiella oxytoca T2L was isolated from the soil of oriental tobacco and demonstrated effective degradation of cis-abienol. The strain was identified through morphological characteristics and 16 S rDNA sequence analysis. Under culture conditions of 30 °C, pH 7.0, 0.5 mg/mL ammonium sulfate, and 1 mg/mL cis-abienol—the degradation rate of cis-abienol by strain T2L reached 68.2% after 96 h. The influence of various carbon and nitrogen sources on the degradation effect of cis-abienol by T2L was examined. Additionally, the impact of pH and temperature on cell growth and cis-abienol degradation was also analyzed. GC-MS analysis indicated that the degradation of cis-abienol by strain T2L generated several potential aroma chemicals, including (+/-)-ambreinolide, sclareol, an analog of amberonne (isomer 3), and an analog of sclaral (sclareolide lactol), which resembled the composition of natural ambergris. This study provides a theoretical foundation for further research on the biodegradation of cis-abienol to high-value aroma compounds.